Game-related performance metrics differentiating winning and losing teams in the Basketball Champions League - Panagiotis F. Foteinakis; Stefania P. Pavlidou (Journal of Physical Education (Maringá), 2025)
This study aimed to identify game-related performance variables that differentiate winning and losing teams in the Basketball Champions League and determine the most significant predictors of game outcomes. Data were collected from 175 games during the 2023-2024 season. The Mann-Whitney U test and logistic regression analysis were employed to evaluate the influence of offensive and defensive metrics on game outcomes. Significant differences were found in key metrics such as shooting percentages, points per game, and defensive rebounds, with winning teams consistently outperforming losing teams. Logistic regression identified steals and defensive rebounds as the strongest predictors of success. Steals increased the odds of victory by 59.6% and defensive rebounds by 48.8%, underscoring the critical role of defensive metrics. Conversely, two-point attempts negatively predicted winning odds, with each additional attempt reducing the likelihood of victory by 32.9%. The findings highlight the importance of efficient shot-making, effective defense, and offensive coordination in basketball performance. These results provide valuable insights for coaches and analysts seeking to enhance team performance and develop effective game strategies.